(untitled) (Nexo Revista Científica, 2021)
A production process was designed for the continuous use of leather shavings from the tanning process to be used as raw material to make a recycled product (reconstituted leather). Its objective is to reuse in a sustainable way the waste of leather shavings from the tanning process without generating new solid waste, since the potential solid waste generated can be used again in the designed production process. This process is divided into three units, the first unit is for the conditioning of the raw material that provides the characteristics to the leather shavings to be processed; the second unit of kneading and molding that mixes shavings of leather, water, resin and; the third third pressing and drying unit that provides the physical and mechanical properties of the developed plate. This proposal allows to obtain an ecological process that will allow the use of leather shavings as raw material for the elaboration of reconstituted leathers; also identify and define the operating parameters, as well as the respective chip, water and resin compositions for the formation of the plaque. Preliminary results show the potential use of leather shavings as raw material to make reconstituted leather without generating negative impacts on the environment.